2020
DOI: 10.3390/genes11101197
|View full text |Cite
|
Sign up to set email alerts
|

Drought-Tolerance Gene Identification Using Genome Comparison and Co-Expression Network Analysis of Chromosome Substitution Lines in Rice

Abstract: Drought stress limits plant growth and productivity. It triggers many responses by inducing changes in plant morphology and physiology. KDML105 rice is a key rice variety in Thailand and is normally grown in the northeastern part of the country. The chromosome segment substitution lines (CSSLs) were developed by transferring putative drought tolerance loci (QTLs) on chromosome 1, 3, 4, 8, or 9 into the KDML105 rice genome. CSSL104 is a drought-tolerant line with higher net photosynthesis and leaf water potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…3a). The drought response of OsSOQ1 is consistent with the previous study [27]. Also studied was the protein level of OsSOQ1 at different developmental stages and in different aboveground tissues in rice.…”
Section: Ossoq1 Is Involved In the Npq Possibly By Regulating Psbssupporting
confidence: 89%
See 1 more Smart Citation
“…3a). The drought response of OsSOQ1 is consistent with the previous study [27]. Also studied was the protein level of OsSOQ1 at different developmental stages and in different aboveground tissues in rice.…”
Section: Ossoq1 Is Involved In the Npq Possibly By Regulating Psbssupporting
confidence: 89%
“…Here, the function analysis of a homolog of Arabidopsis SOQ1, OsSOQ1, also a multi-domain protein in rice, is presented. It has been shown that OsSOQ1 is related to the drought response in rice [27]. Homozygous mutants (ossoq1) were obtained by CRISPR/Cas9 to knockout OsSOQ1.…”
Section: Introductionmentioning
confidence: 99%
“…Water deprivation not only induces physiological changes, but also triggers morphological and stomatal density changes in plant (Punchkhon & al. 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in A under stress conditions was mainly the result of a decrement in g s . Punchkhon et al (2020) recorded that all photosynthetic performance parameters (A, g s and the transpiration rate) significantly decreased (44-70%) in all their studied rice lines under drought stress during the vegetative stage compared with non-stressed plants. In addition, Moonmoon et al (2020) observed that drought reduced all physiological attributes, such as LWP, A and g s .…”
Section: Effects Of Drought Stress On Photosynthetic Function Of Net ...mentioning
confidence: 93%